Demonstrating introductory control systems concepts on inexpensive hardware - Smith, Shane R. (Kansas State University, 2017)
There is a trend in the control literature and in university control education research to develop inexpensive laboratory equipment for control based laboratories. But can using cheaper equipment obfuscate the concepts we are trying to demonstrate in the experiments? To investigate this, lab concepts were examined using an inexpensive platform developed at Kansas State University, Eeva, and compared to the existing lab equipment used in the introductory controls course, the MotorLab. While many lab concepts were successfully demonstrated on the cheaper hardware, they were obscured by higher order effects such as speed filters, back EMF effects, and encoder resolution. The effective operating range of the hardware also suffered from lower saturation limits and higher friction values, making the design of experiments more difficult. Care should be taken when designing inexpensive laboratory equipment to ensure that the lessons desired can still be demonstrated clearly to the students using the equipment.
Keywords: Control systems; Education; Laboratory